Autoethnography, Storytelling, and Life as Lived: A Conversation Between Marcin Kafar and Carolyn Ellis - Kafar, Marcin; Ellis, Carolyn (Przegląd Socjologii Jakościowej, 2014)
This conversation takes place in Warsaw. Carolyn Ellis has come to Poland to accompany Jerry Rawicki, a Warsaw Ghetto survivor, on his first trip back to Poland since the Holocaust. There she arranged to meet Marcin Kafar, a scholar in Poland who has spent time with her at the University of South Florida in Tampa, Florida. During this visit, Marcin assists Carolyn with video recording Jerry’s experiences as they visit Holocaust sites, and Jerry remembers and reflects on his experience. Afterwards, Marcin converses with Carolyn about autoethnography, storytelling, and the importance of life in the context of searching for ethos by academics.